2018
DOI: 10.1097/md.0000000000013043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Imaginary Working Qigong on the psychological well-being of college students

Abstract: Introduction:College students are special populations that are particularly prone to have significantly high level of psychological distress than their community peers. Apparently, the best way to manage stress and mental state is through self-care. The characteristic of Qigong is self-directed and self-healing, which is a traditional Chinese mind-body exercise, which has the potential as a stress management intervention. Imaginary Working Qigong, as a kind of static Qigong, is more perception-oriented and can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…They must not only face various problems in their studies, work, and feelings but also solve problems of interpersonal communication. Without guidance and support, college students could feel anxious and pressured ( Guo et al, 2018 ). A substantial proportion of anxious college students have sub-health problems due to unhealthy living habits, such as drinking, smoking, staying up late and eating irregularly.…”
Section: Introductionmentioning
confidence: 99%
“…They must not only face various problems in their studies, work, and feelings but also solve problems of interpersonal communication. Without guidance and support, college students could feel anxious and pressured ( Guo et al, 2018 ). A substantial proportion of anxious college students have sub-health problems due to unhealthy living habits, such as drinking, smoking, staying up late and eating irregularly.…”
Section: Introductionmentioning
confidence: 99%
“…These studies describe the genomic and epigenetic pathways of stress, focusing on gene expression changes brought about by mind-body therapies. Despite a number of studies supporting the effectiveness of these interventions in lowering the level of stress, [ 13 , 25 , 26 , 27 , 28 ], improving well-being [ 29 , 30 , 31 , 32 ], and academic attainment in student populations [ 33 ], they may also present adverse effects and contraindications [ 34 , 35 , 36 , 37 , 38 ], especially for those individuals who are advised against mild to moderate physical exertion. In addition, mind-body therapies often require training that may be challenging to learn, and they are generally time-consuming to perform.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Finkelstein-Fox, Park, & Riley, 2018;Gallego, Aguilar-Parra, Cangas, Rosado, & Langer, 2016;Meier & Welch, 2016;Running & Hildreth, 2017;Saoji, Mohanty, & Vinchurkar, 2017) Despite a number of studies supporting the effectiveness of these interventions in lowering the level of stress, (Gallego et al, 2016;Nanthakumar, 2018;Stillwell, Vermeesch, & Scott, 2017;Upchurch, Gill, Jiang, Prelip, & Slusser, 2018;Wang & Hagins, 2016), improving well-being (Birtwell, Williams, van Marwijk, Armitage, & Sheffield, 2019;Sarkissian, 2014;Soares & Chan, 2016;Zhang et al, 2018), and academic attainment in student populations (Bennett & Dorjee, 2016), they may also present adverse effects and contraindications. Notwithstanding the scarcity of empirical investigation on this subject, it is reported that mindfulness and meditation may induce temporary neurotic/anxiety symptoms (Dobkin, Irving, & Amar, 2012); mindful meditation, in particular, may induce psychosis, mania, or suicidal ideation especially in those with prior psychiatric morbidity (Wielgosz, Goldberg, Kral, Dunne, & Davidson, 2019); the autogenous training is contraindicated for those who suffer from a number of medical and/or mental conditions, for example, hypertension and psychosis (Brancaleone, 2010); yoga may not be recommended for those who suffer from arthritis (Dobkin et al, 2012); guided imagery may trigger post-traumatic stress symptom in patients with a history of previous emotional, sexual, or physical abuse (American Academy of Pediatrics, 2016); and qigong is contraindicated for those who have suffered from mental illness or severe consumptive disease, cerebrovascular disease, and severe cardiovascular, liver, kidney, gastrointestinal and hematological diseases, and musculoskeletal system diseases (Guo et al, 2018).…”
mentioning
confidence: 99%